ESTIMATION OF PERMEABILITY AND POROSITY VALUES FROM TWO INTERACTING OIL WELLS - SEPTIANI (NIM : 10108001); Pembimbing : Dr. Agus Yodi Gunawan , ANGGITA
The Ensemble Kalman Filter can be used as one of the methods to estimate reservoir parameters, such as porosity and permeability. These parameters play important role to characterize the reservoir properties. The Ensemble Kalman Filter method is one of the sequential estimation of a parameter estimation method which uses the parameter at (t-1), called the prior parameter to estimate the parameters at t after the observation at, called the posterior parameter. In this project, EnKF method is used to estimate the reservoir parameters for given pressure data sequentially, and for the case of linear flow of two oil wells, one as a production well and another is as an injection well. The result methodology for this project is firstly using the Laplace Transform in order to find the analytical solution of the diffusivity equation, and then applying the result of the analytical solution to enter the Ensemble Kalman Filter algorithm.